Hallazgos radiográficos en los pies de niños diabéticos. - Licea Puig, Manuel; Carbajal Alfonso, Matilde; Lapinet Estrada, Pedro; Pasin Ramos, Antonio (Revista Cubana de Pediatría, 2023)
Conocer alteraciones óseas en niños con pie diabético.